2018
DOI: 10.3390/chemengineering2030035
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Cd(II) Ion Removal from Aqueous Solution by a Low-Cost Adsorbent Prepared from White Yam (Dioscorea rotundata) Waste Using Batch Sorption

Abstract: An agricultural residue, white yam (Dioscorea rotundata) tuber peel (YTBS), was used for the removal of Cd(II) ion from an aqueous solution using a batch method. The adsorbent was characterized using FTIR, TGA, SEM, EDX, N2 BET, XRD, and XRF. The optimization of sorption variables such as pH, contact time, adsorbent dose, and initial metal ion concentration at 25 °C were also carried out. The results indicated the dependence of sorption on the adsorbate pH and adsorbent dose, while the adsorption system reache… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 139 publications
0
20
0
3
Order By: Relevance
“…Therefore, there is a need to find alternative adsorbents of comparable effectiveness with lower costs for the removal of heavy metals. Several authors have used raw adsorbents for the removal of toxic heavy metal ions from aqueous solutions and industrial wastewater (Tasar et al 2014;Ali and Saeed 2015;Asif and Chen 2017;Asuquo et al 2018) and these were found to be promising.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, there is a need to find alternative adsorbents of comparable effectiveness with lower costs for the removal of heavy metals. Several authors have used raw adsorbents for the removal of toxic heavy metal ions from aqueous solutions and industrial wastewater (Tasar et al 2014;Ali and Saeed 2015;Asif and Chen 2017;Asuquo et al 2018) and these were found to be promising.…”
Section: Introductionmentioning
confidence: 99%
“…In order to separate and remove heavy metal pollutants from water bodies, several technologies, such as adsorption, ion exchange, membrane separation, coagulation/flocculation, reverse osmosis, electrodialysis, and chemical precipitation 2 , have been developed in recent years. Out of these technologies, adsorption is considered the most promising method because of its high efficiency, low cost, simple operation, fast response, and environmental friendliness 1,8,9 .…”
Section: Introductionmentioning
confidence: 99%
“…In other words, Cd(II) and other cations were adsorbing on the less carboxylic sites [39], making the peak disappear. Asuquo et al [46] also pointed out that the decrease in the wavenumber of the peak at 1734 cm −1 that was a characteristic for the C=O group from the carboxylic acid and its disappearance could be used as direct evidence for the interaction between Cd(II) and these adsorbents during adsorption. The –O–CH 3 group of lignin, and Si–O–Si or Si–O groups from the rice straw biochar participated in the association with Cd(II).…”
Section: Discussionmentioning
confidence: 99%